2001
DOI: 10.1007/bf02234782
|View full text |Cite
|
Sign up to set email alerts
|

Short-term sacral nerve stimulation for functional anorectal and urinary disturbances: Results in 40 patients

Abstract: In functional bowel disorders short-term sacral nerve stimulation seems to be a useful diagnostic tool to assess patients for a minor invasive therapy alternative to conventional surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
123
1
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(133 citation statements)
references
References 11 publications
4
123
1
5
Order By: Relevance
“…10,11 The effect on sensation appears less clear; however, this research and other larger studies have suggested altered rectal sensation. 13 This paper reports the first attempt to examine the autonomic nerves directly and illustrated a rapidly reversible, dose-dependent effect up to a threshold of 1.0-V. This finding may have implications for the level of future therapeutic stimulation.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…10,11 The effect on sensation appears less clear; however, this research and other larger studies have suggested altered rectal sensation. 13 This paper reports the first attempt to examine the autonomic nerves directly and illustrated a rapidly reversible, dose-dependent effect up to a threshold of 1.0-V. This finding may have implications for the level of future therapeutic stimulation.…”
Section: Discussionmentioning
confidence: 82%
“…One showed an improvement in 2 of 8 patients, 12 the second showed a subjective improvement. 13 This led to the first world implants of a sacral nerve stimulator for intractable idiopathic constipation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to respond may be due to a number of factors such as lead displacement, genuine absence of response or neurological injury. SNS is not effective in patients with a high complete spinal cord transection [31]. Indeed, neurological integrity would seem to be a pre-requisite as the technique has not been used successfully in patients with complete pudendal nerve lesions [28, 31].…”
Section: Resultsmentioning
confidence: 99%
“…Sacral nerve stimulation (SNS) has been used since 1967 to activate bladder voiding (91,132,182,241), to treat bladder incontinence (20,34,44,59,78,108,119,120,122,221,229), to alleviate pelvic pain (1,38,190,279), to prevent fecal incontinence (50,(72)(73)(74)103,153), and to relieve constipation (56,128,133,134,161,166,167,186,189,248,252,272 (87,112,138,147,198,199,219) led to many devices (152,201) for improving walking (81,237), activating hand function (24) through voice commands (94), enhancing coughing (154), and even relieving seating pressures (65). Called neuroprostheses (25,193), these devices often are designed to correct specific deficits, such as foot drop (27,217,245) and hand grasp weakness (47,249,267).…”
Section: Peripheral Nerve Stimulationmentioning
confidence: 99%